Thermal Fatigue of Die-Casting Dies: An Overview - Hassan, A. Abdulhadi; S. N., Aqida; M., Ishak; Mohammed, Ghusoon R. (EDP Sciences, 2016)
Coupled studies by experimental and numerical simulations are necessary for an increased understanding of the material behaviour as related to the interaction between the thermal and mechanical conditions. This paper focus on the mechanisms of thermal fatigue in the failure of dies and cores used in the die casting of aluminum alloys. The thermal fatigue resistance is expressed by two crack parameters which are the average maximum crack and the average cracked area. Samples of various types of H13 steel were compared with a standard H13 steel by testing under identical thermal fatigue cycles. To determine the thermal constraint developed in the sample during the test, a finite difference technique was used to obtain the temperature distribution, based on temperature measurements at the boundaries. The resulting stresses and strains were computed, and the strain calculated at the edge or weakest point of the sample was used to correlate the number of cycles to crack initiation. As the strain at the edge increased, the number of cycles to failure decreased. The influence of various factors on thermal fatigue behavior was studied including austenitizing temperature, surface condition, stress relieving, casting, vacuum melting, and resulfurization. The thermal fatigue resistance improved as the austenitizing temperature increased from 1750 to 2050ºF.